KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP KELAS VIII PADA MATERI BANGUN DATAR - Susanti, Rita; Novtiar, Chandra (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2018)
The development of creative thinking is one of the focus of mathematics learning. This study aims to determine the level of creative thinking ability of students of SMP Krida Utama class VIII on the flat wake material. The sample in this study amounted to 5 students, the instrument used as many as 4 pieces of questions in the form of a description problem. Currently the development of creativity has become one of the focus of learning that can be developed through the teaching process, including mathematics learning. One of the topics in mathematics that has the potential as a means of developing the creativity of the attainment of creative thinking ability is the wake-up topic. In this study the number of students who meet the fluency indicator (fluency) as much as 65%, flexibility as much as 70%, 50% originality, elaboration as much as 40%.